Fabrication Accuracy and Material Properties of Spiral-laminated CFRP Specimens Made of UD Prepreg. (2017) - Kondo, Kenta; Matsumoto, Takashi
Abstract: CFRP has attracted attention as a material with lightweight, high strength and durability. Meanwhile, application of biomimetics is also receiving attention in recent years. In this study, a mantis shrimp crab is focused on. It has quite firm tissue forming spiral-laminated fibers. With such backgrounds, we produced spiral-laminated CFRP specimens. This paper describes the production processes and the results of bending tests. The purpose is to consider the influence to the material properties by the fabrication accuracy. As a result, the thinner a specimen is, the higher the maximum stress becomes. It was concluded that thinner thickness means stronger bonding between carbon fibers.